THE IMPACT OF STRATEGIC AGILITY IN THE FOR ACHIEVING SUSTAINABLE TOURISM DEVELOPMENT AN EXPLORATORY STUDY IN THE MINISTRY OF CULTURE, TOURISM AND ANTIQUITIES - Miaad Kareem; Prof. Dr. Dina Hamid Jamal (Scholar Express Journals, 2023)
This study aimed test influence relationship of variables of current study, as strategic agility(SA) is an independent variable through dimensions in achieving sustainable tourism(AST) development as an approved variable a sample of leaders in Iraqi Tourism Authority, in Ministry of Culture, Tourism , Antiquities, by reality of(190) A questionnaire distributed to (general managers, assistant general manager, heads of departments, people's officials) was distributed to them exclusively , comprehensively to survey their opinions About availability of the researched variables in order to identify the relationships targeted by the study, so I learned from them(186(and at discharged excluded(2) Including fact that is not valid statistical analysis to be study sample (184), these variables interacted to form general framework for research, the main and sub-hypotheses emanated from them in order achieve the research objective
Keywords: strategic agility; sustainable tourism development